Capacitive Mixing for Harvesting the Free Energy of Solutions at Different Concentrations - Renéa van Roij; Doriano Brogioli; Francesco Mantegazza; Domenico Salerno; Roberto Ziano; Raúl A. Rica (Entropy, 2013)
An enormous dissipation of the order of 2 kJ/L takes place during the natural mixing process of fresh river water entering the salty sea. “Capacitive mixing” is a promising technique to efficiently harvest this energy in an environmentally clean and sustainable fashion. This method has its roots in the ability to store a very large amount of electric charge inside supercapacitor or battery electrodes dipped in a saline solution. Three different schemes have been studied so far, namely, Capacitive Double Layer Expansion (CDLE), Capacitive Donnan Potential (CDP) and Mixing Entropy Battery (MEB), respectively based on the variation upon salinity change of the electric double layer capacity, on the Donnan membrane potential, and on the electrochemical energy of intercalated ions.